2008
DOI: 10.1037/0735-7044.122.4.943
|View full text |Cite
|
Sign up to set email alerts
|

Exercise is associated with reduction in the anxiogenic effect of mCPP on acoustic startle.

Abstract: Voluntary exercise has been associated with reduced anxiety across several animal models. Manipulation of central 5-HT can alter anxiety-like behaviors and administration of the 5-HT agonist metachlorophenylpiperazine (mCPP) increases anxiety in rodents and humans. To examine whether the anxiolytic effect of exercise is associated with an alteration in 5-HT systems, we examined the anxiogenic effect of mCPP in exercising and nonexercising mice. C57BL/6J mice were given 2 weeks of free access to either a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 91 publications
10
46
0
Order By: Relevance
“…However, despite the observation that the CORT response to stress was shorter lived in wheel-running mice, we did not observe changes in either peripheral or central HPA-axis negative feedback. Consistent with previous work from our laboratory (Fox et al, 2008;Salam et al, 2009), wheel running was associated with reduced anxiety-like behavior. However, it was unclear whether the observed changes in the HPA axis actually contributed to the anxiolytic effect of wheel running.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, despite the observation that the CORT response to stress was shorter lived in wheel-running mice, we did not observe changes in either peripheral or central HPA-axis negative feedback. Consistent with previous work from our laboratory (Fox et al, 2008;Salam et al, 2009), wheel running was associated with reduced anxiety-like behavior. However, it was unclear whether the observed changes in the HPA axis actually contributed to the anxiolytic effect of wheel running.…”
Section: Discussionsupporting
confidence: 91%
“…In humans, exercise is associated with a reduced incidence of stress-related psychopathology (De Moor et al, 2006;Dunn et al, 2001;Herring et al, 2010;Lawlor and Hopker, 2001), and in rodents, voluntary wheel running is associated with reduced anxiety-and depression-like behaviors (Binder et al, 2004;Fox et al, 2008;Greenwood et al, 2005;Greenwood et al, 2003;Salam et al, 2009;Sciolino et al, 2012). For example, we have shown that 2 weeks of home cage wheel running in C57BL/6J mice reduces acoustic startle amplitude, reduces stress-induced hyperthermia, diminishes anxiety-like behavior in the open field, and reduces the anxiogenic effect of the serotonin agonist m-chlorophenylpiperazine (mCPP, Fox et al, 2008;Salam et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety was assessed following Day 21 of wheel access with stressinduced hyperthermia (SIH) and with a meta-chlorophenylpiperazine (mCPP) challenge. We have shown that exercise reduces both SIH and the anxiogenic effect of mCPP (Fox, Hammack, & Falls, 2008;Salam et al, 2009). The anxiogenic serotonin agonist mCPP (0.3 mg/kg; 10 ml/kg volume; ip) or vehicle (0.9% saline) was administered 15 min before an acoustic startle test.…”
Section: Methodsmentioning
confidence: 99%
“…The startle test was identical to those described above. Startle was assessed in each mouse following both mCPP and vehicle injection in a counterbalanced within-subject fashion witb 48 hr between tests (Fox et al, 2008). The mCPP challenge was followed 48 hr later by assessment of SIH in which core body temperature was assessed at baseline and 10 min later using a small rectal probe (Salam et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate, short-term exercise (five daily treadmill sessions 1 h) has not been shown to alter serotonin 5-HT 1A receptors or anxiety-related behaviours (e.g., decreased activity in open spaces, as measured using an elevatedplus maze) in rodents (Chaouloff, 1994). In contrast, the anxiogenic properties of the 5-HT agonist metachlorophenylpiperazine (mCPP) are attenuated with longer-term (2 weeks access to a running wheel) exercise (Fox, Hammack, & Falls, 2008). In another report, longer-term exercise was associated with enhanced sensitivity of 5-HT 2 receptors, in combination with subsensitivity of 5-HT 1A autoreceptors (Dey, 1994).…”
Section: Mechanisms Of Actionmentioning
confidence: 98%